Metabolomic profiling reveals the relationship between taste-related metabolites and roasted aroma in aged pork. (1st February 2022) - Tamura, Yoshio; Iwatoh, Shinji; Miyaura, Kazutoshi; Asikin, Yonathan; Kusano, Miyako
Abstract: Although postmortem aging of pork improves its umami taste when roasted, the relationship between roasted aroma and taste has not been investigated. Therefore, in this study, we investigated the role of taste-related metabolites in the aroma composition of roasted meat during postmortem aging. Comprehensive metabolomic analyses of taste-related metabolites and volatile organic compounds in aged pork were conducted by gas chromatography-time-of-flight mass spectrometry. Taste-related metabolites, including amino acids, sugars, fatty acids, and nucleic acids, accumulated with age. Among the detected aroma compounds, benzeneacetaldehyde and 2, 5-dimethyl-3-(3-methylbutyl)-pyrazine levels increased with age; these compounds potentially contribute to roasty and meaty aromas. Furthermore, there was a positive correlation between aroma compounds and their precursors in raw meat; some amino acids contributed to the generation of benzeneacetaldehyde, 3-methylbutanal, 3-ethyl-2, 5-dimethyl-pyrazine, and 2, 5-dimethyl-3-(3-methylbutyl)-pyrazine via the Maillard reaction. These results confirm that the changes in taste-related metabolites in raw meat affect the specific aroma compositions of roasted meat. Highlights: Taste-related metabolites in aged pork were analyzed by metabolomic profiling. Benzeneacetaldehyde and 2, 5-dimethyl-3-(3-methylbutyl)-pyrazine accumulate with age. Roasty and meaty aroma compounds are generated via the Maillard reaction. Taste-related metabolites in aged raw meat alter the aroma profile of roasted pork. Trace volatile organic compounds also modulate the aroma profile of aged pork.